PUBLIC INFORMATION DISCLOSURE IN GOOD GOVERNANCE FOR THE PREVENTION OF CORRUPTION IN INDONESIA (Study: The Implementation of Public Information Disclosure in LIPI) - Dewi Saraswati (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTThe right to information is crucial because the more open the public scrutiny of the state administration, the more accountable the state administration is. Each public agency has the obligation to open public access to information relating to the Public Agency for the wider community, especially LIPI (Indonesian Institute of Sciences). Therefore, it is important to examine the implementation of the Public Information in LIPI in order to prevent acts of corruption. Based on the results of the research, it can be concluded that as the implementation of good governance, especially the embodiment of the principles of transparency in order to prevent acts of corruption, LIPI has conducted Public Information Disclosure. LIPI has provided Whistle-blowing System (WBS) as a means to facilitate information providers who want to report allegations of corruption in LIPI. For general information requests related to LIPI can be accessed via http://wbs.lipi.go.id/